Single-Session Computerized Cognitive Behavioral Therapy for Dental Anxiety: A Case Series. (February 2016) - Potter, Carrie M.; Jensen, Dane; Kinner, Dina G.; Tellez, Marisol; Ismail, Amid; Heimberg, Richard G.
Therapy interventions for dental anxiety that can be easily implemented in dental health care settings are needed. A series of six case studies is presented to demonstrate the feasibility, acceptability, and initial efficacy of a single-session computerized cognitive behavioral therapy intervention for dental anxiety. Six patients at a community dental clinic (five females, M age = 49.50, SD = 10.48) who were identified as having high dental anxiety on the Modified Dental Anxiety Scale (MDAS) participated in this uncontrolled pilot trial. All patients completed pre-treatment assessments of dental anxiety and the computerized therapy during the hour before a scheduled dental appointment, and five of six patients completed a 1-month follow-up assessment. All six of the patients were able to complete the intervention with minimal assistance and reported that they were very satisfied with the therapy. Three of the five patients available for follow-up assessment demonstrated clinically significant reductions in their dental anxiety, with MDAS scores dropping from the high range to the low range. Findings provide preliminary support for the feasibility, acceptability, and efficacy of this computerized dental anxiety intervention. Implications for the dissemination of this intervention within dental health care settings and improvement of anxious patients' access to dental care are discussed.